Exploring interventions to support life participation for adults with chronic kidney disease: a scoping review - Mikaela Correa; Roaa Hussam; Janine Farragher (BMC Nephrology)
Abstract Background Individuals with chronic kidney disease (CKD) can experience significant health-related challenges that affect their life participation. Recent studies have identified life participation as a top priority for adults with CKD. This scoping review aims to comprehensively identify studies of interventions that targeted life participation outcomes in adults with predialysis CKD, and identify gaps in the literature. Methods This scoping review followed the Joanna Briggs Institute (JBI) methodology. Five electronic databases were searched with additional sources identified through backwards chaining. Title and abstract screening were conducted independently by four screeners after initial inter-rater calibration, and full text screening and data extraction were undertaken by two researchers in duplicate. Data analysis was completed using descriptive statistics and narrative synthesis. Results This scoping review identified twenty-three studies that examined interventions to support life participation in the CKD population. No studies targeted life participation as a primary outcome. When categorizing studies via the Canadian Model of Occupational Performance and Engagement (CMOP-E) the majority (87%) of interventions targeted personal-physical mechanisms of disability, with a predominant focus on pharmacological (48%) or exercise (35%) interventions. Dedicated outcome measures for life participation were rarely used, with the role-physical, role-emotional and social functioning subscales of the SF-36 quality of life assessment being the most common life participation outcome measures. Conclusions This scoping review highlights a lack of research and prioritization of life participation in CKD. It demonstrates the narrow scope of intervention approaches used to support life participation, and limitations in how studies assess life participation. These gaps indicate a need for further research to support this top priority health outcome for the CKD community. Clinical trial number As this is a scoping review, no clinical trial number is provided.